2021
DOI: 10.3390/biomedicines9091217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of WAVE2 Signaling in Cancer

Abstract: The Wiskott–Aldrich syndrome protein (WASP) and WASP family verprolin-homologous protein (WAVE)—WAVE1, WAVE2 and WAVE3 regulate rapid reorganization of cortical actin filaments and have been shown to form a key link between small GTPases and the actin cytoskeleton. Upon receiving upstream signals from Rho-family GTPases, the WASP and WAVE family proteins play a significant role in polymerization of actin cytoskeleton through activation of actin-related protein 2/3 complex (Arp2/3). The Arp2/3 complex, once act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…The mechanism involves the exposure of the WCA domain of WAVE that binds and activates Arp2/3 8,9 . The RAC1-WAVE-Arp2/3 pathway is critical for development and normal adult life but is also involved in cancer [10][11][12] . Genes encoding subunits of the WAVE and Arp2/3 complexes are overexpressed in a variety of cancers, and this overexpression is associated with high tumor grade and poor patient prognosis 13 .…”
mentioning
confidence: 99%
“…The mechanism involves the exposure of the WCA domain of WAVE that binds and activates Arp2/3 8,9 . The RAC1-WAVE-Arp2/3 pathway is critical for development and normal adult life but is also involved in cancer [10][11][12] . Genes encoding subunits of the WAVE and Arp2/3 complexes are overexpressed in a variety of cancers, and this overexpression is associated with high tumor grade and poor patient prognosis 13 .…”
mentioning
confidence: 99%
“…Colorectal cancer has become the third leading cause of cancer-related deaths in humans, accounting for 8.7% of all cancer deaths. [ 1 ] By immunohistochemistry, Otsubo et al [ 53 ] discovered significant overexpression of Arp2 and Arp3 proteins in cancer cells and stromal cells in 175 colorectal cancer specimens, whereas Arp2 and Arp3 were not expressed in normal colorectal mucosal epithelial or stromal cells. They proposed that stromal cells expressing Arp2 and Arp3 create a microenvironment that promotes cancer cell invasion prior to invasion.…”
Section: Role Of the Arp2/3 Complex In Cancermentioning
confidence: 99%
“…Cancer cell invasion and migration are key components of cancer metastasis, which refer to the ability of cancer cells to move and cross the basement membrane and extracellular matrix, eventually moving and infiltrating into the surrounding tissue. [ 1 ] Cancer invasion and metastasis are complex processes that involve multiple cellular interactions and signaling pathways. However, cancer cells must undergo changes in actin cytoskeleton regulation and produce protrusion structures on their membranes, such as lamellipodia, invadopodia, and filopodia, in order to acquire a migratory phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…According to some research, WAVE2 is expressed more in hematopoietic cells and the deficiency of WAVE2 causes abnormal activation of T cells. It has also been reported that WAVE2-related signaling pathways play crucial roles in the invasion process and metastasis keeping of cancer cells and may be a novel target for cancer therapy in future ( 76 78 ). Scientists have found that WAVE 2 KO mice have severe autoimmune disease and inflammatory response compared to the WT controls ( 79 , 80 ).…”
Section: Wave2 Maintains T Cell Homeostasis and Function Via Binding ...mentioning
confidence: 99%